O protagonismo dos cristãos e o poder na Igreja - Bitencourt, Henrique Vicente de (2008)
This study had as objective to verify if Christians from the Catholic Church, in Lages/SC, can develop their social protagonism and in which level, from the participation proposed by the Catholic Church. At first, it was important to understand the matter of sacred from its history and how it has been changing in religious experience, that is, in a religion more and more institutionalized. That process can be verified into the Christianity, rendering bureaucratic to it so that it was important to ask: is there condition in this Church for humans development on their several subjective spiritual expressions? In this study, protagonism was understood as the human s possibility to develop himself/herself as a social actor, able to perform an active citizenship in different levels (personal and social), making the difference into the society, the same that happened with the Christians from the communities during the three first centuries of the Catholic Church. After analyzing the history of the Catholic Church practices, from global to local levels (Lages), it was made a research with people from 08 parishes (Lages/SC), in order to (1) verify if Christians feel themselves as actors of their actions and if their faith practices contribute on their actions in civil society as well; and (2) detect if there is the practice of the protagonism. It was possible to perceive an accentuated negative sense of the Catholic Christians in relation to the Church and a camouflaged but conscious cry for changes, mainly in changing that Church rigidly hierarchical with a centralized power. They manifested a strong desire for a Church as a community of brothers and sisters , using as reference the practice of the first Christians, who lived in a permanent dialectics among institution, multiplicity of charismas and prophecy